Altered Divalent Ion Metabolism in Different Stages of Chronic Renal Failure - Islam, AKMM; Rahman, H; Rashid, HU (TAJ: Journal of Teachers Association, 2009)
A total of 50 patients (male-28, female-22), in diferent stages of chronic renal failure (Mild, CCR 30-50ml/min/1.73m2n=17; Moderate, CCR 10 to 29 ml/ min /1.73 m2, n=15and Severe, CCR < 10 ml / min /1.73 m2, n=18) and 23 healthy controls (CCR 60 to 120 ml / min /1.73 m2, male - 11, female -12) were studied in the Department of Nephrology BSMMU, Dhaka to see the alteration of divalent ion metabolism in different stages of chronic renal failure. Mean age of the patients were 42.98 ± 14.51 years. The level of serum calcium was significantly lower among the patients of moderate and severe chronic renal failure. Serum inorganic phosphate level was significantly high among the patients of severe chronic renal failure than those of control group. It is concluded that hypocalcaemia and hyperphosphataemia occur in the chronic renal failure patients and these are more marked in advanced chronic renal failure. doi: 10.3329/taj.v16i1.3894 TAJ June 2003; Vol.16(1): 8-11